Concepções sobre altas habilidades/superdotação e prática docente - Bahiense, Taisa Rodrigues Smarssaro (2013)
The present study aimed to explore the conceptions of Elementary School teachers from public in Vitória – ES about high abilities/giftedness (HA/GT). 20 teachers that teach portuguese and mathematic for students from elementary school, from 6th to 9th grade, were the subjects of this research. With the purpose of data collection an interview script containing questions about the conceptualization of HA/GT for teachers and about their education and professional practice, and four stories about myths regarding HA/GT. Data collection was supported theoretically in Piaget's Clinical Method. The results of this research show that, in general, there is a complaint from teachers about their preparedness to deal with students with HA/GT. The data also showed that most of the educators believe that the ability / talent must exist to some degree in the individual, but the environment is important for developing the potential of that person. It also showed that, for the most part, the teachers argue that these students need to have a special service and the person with HA/GT not need to master all subjects in the school curriculum. Finally, revealed that teachers have great concern with the socialization of the student who has HA/GT. Thus, it is expected that this work will contribute to the advancement of the discussion on the theme of HA/GT, still scarce today, offering theoretical and methodological work to support teachers in the area.